Analysis of the microstructure of microbial solidified sand and engineering residue based on CT scanning - Minxia Zhang; Congrui Feng; Xiang He; Ping Xu (Biogeotechnics)
A close relationship exists between the pore network structure of microbial solidified soil and its macroscopic mechanical properties. The microbial solidified engineering residue and sand were scanned by computed tomography (CT), and a three-dimensional model of the sample was established by digital image processing. A spatial pore network ball-stick model of the representative elementary volume (REV) was established, and the REV parameters of the sample were calculated. The pore radius, throat radius, pore coordination number, and throat length were normally distributed. The soil particle size was larger after solidification. The calcium carbonate content of the microbial solidified engineering residue’s consolidated layer decreased with the soil depth, the porosity increased, the pore and throat network developed, and the ultimate structure was relatively stable. The calcium carbonate content of the microbial solidified sand’s consolidated layer decreased and increased with the soil depth. The content reached the maximum, the hardness of the consolidated layer was the highest, and the development of the pore and throat network was optimum at a depth of 10–15 mm.